Penerapan Corporate Social Responsibility, Corporate Governance, Komitmen Manajemen dan Etika Bisnis Terhadap Reputasi Organisasi Pada Perusahaan PT. Pertamina di Kabupaten Muaro Jambi - Reni Yustien; Andi Mirdah (Magister Ilmu Akuntansi Universitas Jambi, 2020)
Corporate Social Responsibility (CSR) is a concept that can bring companies to carry out its responsibilities to the environment and society. Companies are required to be socially responsible. This happens because there are economic disparities between businesses that often have negative impacts on the environment. It is the background of the emergence of the concept of CSR. Along with the rapid development of the world sector. Various private sector, governments, organizations, communities, education, seeks to define and promote the social responsibility of the business sector in relation to society and the environment. PT. Pertamina, which is in the district Muaro has implemented several CSR activities by paying attention and contribution to the development community around its area of ​​operations through its Corporate Social Responsibility (CSR) based on management planning. The company's role in managing the resources responsible for managing the resources entrusted by society with both a liability (compulsory). The implementation of CSR in companies pertamina impact also on the implementation of CSR programs with a level of consistency to the Corporate Governance, Management Commitment, Business Ethics as a system that directs and controls the company as a form of liability because the regulations governing the balance of the company with the environment that is realized through CSR. This study aims to prove the influence of Corporate Social Responsibility (CSR), Corporate Governance, Management Commitment, Business Ethics on Organizational Reputation at Pertamina Company located in the district Muaro Jambi Province. Keywords: Corporate Social Responsibility (CSR), Corporate Governance Practices, Management Commitment, Business Ethics and Organizational Reputation